A comparative analysis of chloroplast genomes revealed the chloroplast heteroplasmy of Artemisia annua - Ding, Xiaoxia; Pan, Hengyu; Shi, Peiqi; Zhao, Siyu; Bao, Shengye; Zhong, Shan; Dai, Chunyan; Chen, Jieting; Gong, Lu; Zhang, Danchun; Qiu, Xiaohui; Liao, Baosheng; et al. (Frontiers in Pharmacology, 2024)
Artemisia annua L. is the main source of artemisinin, an antimalarial drug. High diversity of morphological characteristics and artemisinin contents of A. annua has affected the stable production of artemisinin while efficient discrimination method of A. annua strains is not available. The complete chloroplast (cp) genomes of 38 A. annua strains were assembled and analyzed in this study. Phylogenetic analysis of Artemisia species showed that distinct intraspecific divergence occurred in A. annua strains. A total of 38 A. annua strains were divided into two distinct lineages, one lineage containing widely-distributed strains and the other lineage only containing strains from northern China. The A. annua cp genomes ranged from 150, 953 to 150, 974 bp and contained 131 genes, and no presence or absence variation of genes was observed. The IRs and SC junctions were located in rps19 and ycf1, respectively, without IR contraction observed. Rich sequence polymorphisms were observed among A. annua strains, and a total of 60 polymorphic sites representing 14 haplotypes were identified which unfolding the cpDNA heteroplasmy of A. annua. In conclusion, this study provided valuable resource for A. annua strains identification and provided new insights into the evolutionary characteristics of A. annua.